A Dose-Response Relationship to Radiotherapy for Cutaneous Lesions of Langerhans Cell Histiocytosis - Mark K. Farrugia; Carl Morrison; Francisco Hernandez-Ilizaliturri; Saif Aljabab (Case Reports in Oncological Medicine)
Langerhans cell histiocytosis (LCH) is a rare disease, afflicting approximately 4.6 and 1-2 per 1 million children and adults, respectively. While LCH can involve numerous organ systems such as the lung or bone, it is uncommon for the disease to be limited to the skin. Radiotherapy has an established role for osseous lesions. However, the efficacy and dose for nonosseous manifestations of the disease are not well described. In the current case report, we detail a 49-year-old adult male with skin-limited LCH requiring palliative radiotherapy (RT) to numerous sites for pain control. The patient was initially diagnosed and treated with single agent cytarabine for approximately 6 months. Despite treatment, he had little symptomatic response of his cutaneous lesions. We delivered a single dose of 8 Gray (Gy) to 3 separate skin lesions, including the bilateral groin, right popliteal region, and right axillary lesion, which resulted in pain reduction and partial response at four-month follow-up. Subsequently, we decided to treat the left axillary untreated lesion to a higher dose of 24 Gy in 12 fractions. At four-month follow-up, the left axilla RT resulted in complete clinical response and improved pain control compared to the right axilla. Following RT treatments, the patient was found to have a BRAF mutation, and vemurafenib was initiated. Further follow-up with positron emissions tomography demonstrated complete metabolic response in numerous disease areas, including both axillae. Based on this case report’s findings, a higher radiotherapy dose may be more effective for treating cutaneous LCH.